Ministry of Trade and Industry Decree No. 259 of the Year 2020 = وزارة التجارة والصناعة قرار رقم 259 لسنة 2020 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic